Abrindo a caixa-preta de uma sequência didática: uma análise ator-rede da aprendizagem profissional docente de um professor de Biologia - Victor Marcondes de Freitas Santos (2016)
This research aimed to open the black box of a didactic sequence in order to analyze the teaching practice and the formation of a Biology teacher using Actor-Network Theory as theoretical-analytical framework. To achieve this goal, we investigated a Biology teacher of basic education involved on a collaborative research and intervention project contemplated by a public notice published by the Brazilian research funding agencies (FAPEMIG/CAPES), which gets the production and application of didactic sequences based on Science, Technology, Society and Enviroment curricular approach and guided by socio-technical or scientific-technical issues. Theoretically, we have situated our work on two Education research areas: investigative lines that guide the researches on the use of didactic sequences and references from the field of teacher education studies. In doing so, we have used the theoretical-analytical framework from the Actor-Network Theory, an approach that treats entities as effects of relationships and seeks to explore the configuration and reconfiguration of these ones. In order to collect data based on Latourian Ethnography, we achieved the participant observation during the year of 2014 in two subjects: Biology and Environment and Natural Resources. The generated data of this research came from classroom audio and video records and field notebook notes. In the data analysis we described episodes related to the production and application of the first didactic sequence entitled "Environmental Impact Studies", which was produced by the basic education teacher and by the collaborative group. The work results enabled us to examine which skills, acquirements, knowledge and learning professionals teachers have emerged and were performed, since we have assumed that these are produced effects through human and non-human entities teachers interactions, immersed in the sociomaterial network provided by the didactic sequence.